Taxonomic composition and synanthropic characteristic of woody plant community on Petrovsky waste rock dumps (Kryvorizhzhya) (Ecological Bulletin of Kryvyi Rih District, 2019)
The study of taxonomic composition and ecological characteristics of wood species on devastated lands as a theoretical basis for the phytomelioration of environment remains relevant nowadays. It was discovered 32 species, 25 genera and 15 families in the course of the analysis of woody plant community from devastated lands of Petrovsky waste rock dumps. Among them, allochthonous species (59.38%) have an advantage over autochthonous (40.63%) according to the quantitative indicators. It was established, hemiapophytes predominate among apophytesspecies andneophytes predominate among anthropophytesaccording to the time of entry, according to the method of invasion ergasiophytes, according to the degree of adaptation ergasiophytes and agriophytes. The results of our analysis indicate that the investigated woody plant  ommunitycorresponds to the conditions of localization.
Keywords: tree species; synanthropic species; taxonomic and ecological characteristics; devastated lands; Petrovsky waste rock dumps; Kryvorizhzhya